A new echinoderm faunule from the Lower Jurassic (Pliensbachian) of southern Sweden - Hunter, Aaron; Rees, J. (Geological Society of Denmark, 2010)
In Sweden, Jurassic echinoderms are extremely rare. This present study documents an Early Jurassic echinoderm assemblage collected from a temporary exposure near Helsingborg in Skåne, southern Sweden, which includes a previously undescribed species of isocrinid crinoid, Isocrinus ranae sp. nov., and an acrosaleniid echinoid. The Swedish specimens demonstrate that even limited echino- derm material from small exposures can be assigned to a high systematic level and provide data of considerable significance to the evolution of the group as a whole.